Load Auditory Feedback Boosts Crutch Usage in Subjects With Central Nervous System Lesions: A Pilot Study - Tamburella, Federica; Lorusso, Matteo; Tagliamonte, Nevio Luigi; Bentivoglio, Francesca; Bigioni, Alessandra; Pisotta, Iolanda; Lancini, Matteo; Pasinetti, Simone; Ghidelli, Marco; Masciullo, Marcella; Saraceni, Vincenzo Maria; Molinari, Marco (Frontiers in Neurology, 2021)
Background: Crutches are the most common walking aids prescribed to improve mobility in subjects with central nervous system (CNS) lesions. To increase adherence to the appropriate level of crutch usage, providing load-related auditory feedback (aFB) may be a useful approach. We sensorized forearm crutches and developed a custom software to provide aFB information to both user and physical therapist (PhT). Aim: Evaluate aFB effects on load control during gait by a self-controlled case series trial. Methods: A single experimental session was conducted enrolling 12 CNS lesioned participants. Load on crutch was recorded during 10-metre walk test performed with and without aFB. In both cases, crutch load data and gait speed were recorded. Usability and satisfaction questionnaires were administered to participants and PhTs involved. Results: Reliable data were obtained from 8 participants. Results showed that compared to the no FB condition, aFB yielded a significant reduction in the mean load on the crutches during gait (p=0.001). The FB did not influence gait speed or fatigue (p>0.05). The experience questionnaire data indicated a positive experience regarding the use of aFB from both participants’ and PhTs’ perspectives. Conclusion: aFB significantly improves compliance with crutch use and does not affect gait speed or fatigue by improving the load placed on crutches. The FB is perceived by users as helpful, safe, and easy to learn, and does not interfere with attention or concentration while walking. Furthermore, the PhTs consider the system to be useful, easy to learn and reliable.Keywords: auditory feedback, crutches, gait, rehabilitation, adherence.